Thrombogenic Markers in Patients with Hereditary Thrombophilia - Karima Maricel Gondres Legró; Jorge Calá Fernández; Yusmairy Matos Lores; Vivian Robert Tamayo; Lázaro Ibrahim Romero García; Yordanys Páez Candelaria (Revista Finlay)
Foundation: hereditary thrombophilia is defined as the genetically determined tendency to venous thromboembolism, an entity with a significant incidence worldwide. A large percentage of these thrombosis events could be explained from the laboratory. Objective: to characterize hereditary thrombophilias from a humoral clinical point of view and to identify the possible relationship between altered biochemical markers of thrombosis and its recurrence. Method: a descriptive and cross-sectional study was carried out in the hemostasis laboratory of the Saturnino Lora Provincial Teaching Hospital of Santiago de Cuba, over a period of one year. 39 patients were used as a reference: 26 with thrombotic events discharged from the Angiology, Cardiovascular Surgery and Neurology Services, and 13 without a known event, first-line relatives of those patients who had positive thrombophilia markers during the study. The clinical variables analyzed were: age, sex, personal and family history of thrombosis and number of thrombotic events in the patient. Mean, standard deviation and percentages were calculated. Results: protein S deficiency ranked first with 22 (56.4 %). The combination of altered parameters that predominated was protein C and S deficiency with 8 (20.5 %). Two or more altered markers were found in 64.1 %; similar percentages are shown in patients with 1, 2 or more thrombosis events. Conclusion: thrombophilia was presented as a disease that mainly affects women, at intermediate ages of life. In asymptomatic patients with a family history of thrombotic event, without apparent cause, laboratory markers guide the diagnostic approach. The presence of two or more positive thrombogenic markers suggests the occurrence of thrombotic events in this population.